Evaluation of Quality Family Village Best Practice Program in Stunting Control Efforts in Bengkulu Province - Dea Sabrina Putri; Nopia Wati; Agus Ramon; Emi Kosvianti; Bintang Agustina Pratiwi (GLOBAL HEALTH SCIENCE GROUP, 2025)
The West Ring Quality Family Village has families at risk of stunting, so efforts are needed to reduce this condition so that it does not lead to stunting. This study aims to determine the evaluation of the best practice Kampung KB program in efforts to control stunting. This research uses a qualitative method with thematic analysis. This research was conducted in October 2024 with informants consisting of cadres, stakeholders and PLKB. Data collection techniques are carried out through observation, in-depth interviews and documentation, Researchers conducted observations by going to the field to directly observe the implementation of activities and in-depth interviews are conducted using an interview guide containing several questions that form the basis for extracting information from informants. In addition, researchers conducted documentation to collect supporting data such as archives and pictures related to the activities. The collected data was then analyzed through the reduction stage to select relevant information, display to compile data in a systematic form and finally draw conclusions to identify successes and obstacles in the program. Overall, the program has succeeded in increasing understanding, commitment, role and real impact in stunting control, the combination of education, mentoring and cross-sector collaboration provides good results, creating sustainable positive changes in the community. The Best Practice Program in Quality Family Village shows positive results due to the involvement of all parties including cadres, stakeholders, PLKB and the community in preventing stunting and increasing community knowledge related to nutritious food. However, this activity still cannot be said to be effective because there are several obstacles such as toddlers who do not want to eat or only finish a small portion of the portion provided, economic differences between families and budget limitations. This study contributes to science by identifying and looking at the success of best practices in controlling stunting.